Changes on the cell wall composition of tree-ripened “Bartlett” pears (Pyrus communis L.) - Raffo Benegas, Maria Dolores; Ponce, Nora M. Andrea; Sozzi, Gabriel Oscar; Stortz, Carlos Arturo; Vicente, Ariel Roberto (Elsevier, 2019)
Most of the European pear cultivars fail to develop a desirable texture when ripening on the tree. In order to identify some biochemical anomalies that might be associated with this phenomenon, the main differences in cell wall polysaccharides occurring during “Bartlett” pear on-tree ripening were evaluated. Fruit was harvested at 3 different ripening stages (119, 147 and 161 days after anthesis, DAA) namely unripe (UR) mid-ripe (MR) both developing normal texture upon ripening, and late-ripe (LR), which did not result in buttery and juicy fruit. The characterization of cell wall structure was accomplished by determining the monosaccharide composition, yields, and solubility of uronic acids and neutral sugars in fractions extracted by water (WSF), 0.05 M CDTA (CSF), 0.1 M Na2CO3 (NSF), 1 M and 4 M KOH (1KSF and 4KSF). The size exclusion profiles in all the isolated fractions were also determined. In the transition from the UR to the MR stage, glucose from the 4KSF and Ara from all other fractions became markedly solubilized. A slight increase in water-soluble pectin content and depolymerization of the 4KSF and CSF were also found during this period. From the MR to the LR stage, a glucan probably originating in cellulose turnover was found in the 4KSF, and (though at a lower rate) Ara solubilization continued. In contrast, the depolymerization of all wall fractions after day 147 was minimal, and a shift of water soluble pectins toward the CSF was detected. An imbalance in polyuronide degradation, including decreased depolymerization of pectin backbones, together with continuing removal of Ara from RG I, and/or other modifications increasing ionic interactions, may lead fruit which yield an abnormal, mealy texture upon ripening.